Natural resources in Al-Khums municipality: (a study in resource geography): Natural resources in Al-Khums municipality (Elmergib Journal of Human Sciences, 2026)
This study aims to identify the natural resources available in Al-Khums Municipality for current and future utilization. These natural resources include a geographically distinguished location with a moderate maritime climate and abundant sunshine, which is important for producing clean electricity. Winds also blow across the area, which can be harnessed for clean electricity production. Furthermore, the area boasts a diverse geomorphological landscape that has contributed to the presence of various natural resources, including plains with good soil and water resources, as well as diverse natural vegetation. The rock diversity, which includes limestone and other rocks, has contributed to the establishment of a cement industry, which can be expanded within the municipality. Additionally, the presence of several natural beaches covered with a layer of sand, which are of touristic importance, should be noted.
Keywords: Human Resources; Physical Geography; Population; – Distribution